Patient Characteristics, Diagnoses, and Management in a Combined Uveitis–Rheumatology Clinic - Jason Shawver; Amit K. Reddy; Alan G. Palestine; Jason R. Kolfenbach (Ophthalmology and Therapy)
Abstract Introduction Combined uveitis–rheumatology clinics (combined clinics) are a relatively recent clinical care model. Here we report the demographics, ocular and systemic disease characteristics, and medications utilized in patients seen in a combined clinic at a tertiary care hospital in the USA. Methods Medical records were reviewed of patients seen at the Combined Clinic at the University of Colorado Hospital between January 1, 2016 and November 1, 2023. Data including age, sex, referral indication, ocular and systemic inflammatory disease diagnosis, and therapies utilized were obtained. Results A total of 171 patients were included in the study, of which 122 were diagnosed with a systemic inflammatory disease, the most common of which were spondyloarthritis and rheumatoid arthritis. Nearly half of patients referred to the combined clinic with a known ocular inflammatory disease (OID) and suspicion for a systemic process were eventually diagnosed with a systemic disease. The most common associations in patients with both OID and systemic disease were anterior uveitis with spondyloarthritis, and scleritis with rheumatoid arthritis. The most common systemic immunomodulatory therapies (IMT) used were adalimumab, methotrexate, and rituximab. Over 40% of patients underwent a change in IMT during their first evaluation. Conclusions Most patients seen in the combined clinic had both ocular and systemic inflammatory disease and were treated with IMT. Many patients were diagnosed with a systemic inflammatory disease upon evaluation in the combined clinic, and nearly half were recommended to initiate or change IMT at their first visit. This highlights the utility of a combined clinic in the management of these complex patients, in addition to providing logistical benefits to patients and educational opportunities for trainees.